Factors Influencing the Accuracy and Precision of NFC-Based Temperature Monitoring Device (Journal of Fiber Bioengineering and Informatics, 2024)
Near-field communication (NFC) is a short-distance wireless data transmission technology with potentialfor wearable sensors. Xu et al. (2020) developed a battery-free smart textile patch with an NFC antennaand a temperature sensor (STP-NFC) [1]. To address potential issues with the testing protocol thatcould affect the accuracy and precision of temperature measurement from the STP-NFC, a validationexperiment was conducted at a fixed room temperature of ${\rm 20}^◦{\rm C}.$ This was done using a commercialIR imager to compare the results with the STP-NFC results. Results showed excellent accuracy withan average temperature of ${\rm 21.50}^◦{\rm C}$ and a difference of only ${\rm 0.36}^◦{\rm C}$ from an IR imager’s reading. TheSTP-NFC also had excellent precision with a small standard deviation of 0.83. Optimal performancewas achieved with a 6 mm distance, a 150-second time interval, and a 4-second scanning duration foreach scan. Additionally, the gage repeatability and reproducibility (R&R) study has been conducted toassess the STP-NFC measurement system’s consistency, and the STP-NFC’s reproducibility has beendemonstrated. These results have implications for developing reliable wearable medical monitoringdevices using NFC technology.
Keywords: Near Field Communication; Wearable Sensors and Devices; Validation Experiment; Optimal Procedure; Repeatability and Reproducibility.